2023
DOI: 10.1111/aje.13132
|View full text |Cite
|
Sign up to set email alerts
|

Epauletted fruit bats prefer native plants and contribute to seed dispersal in a South African agricultural landscape

Abstract: Fruit bats provide vital ecosystem services through seed dispersal aiding secondary forest regeneration. However, fruit bat species are often persecuted by fruit-growing farmers due to perceived and actual crop damage. In this study, we investigated the dietary components of Epomophorous wahlbergi, Epomophorous crypturus and Rousettus aegyptiacus, which are the three fruit bat species commonly found in litchi orchards and surrounding natural habitats in the Limpopo Province, South Africa. We further explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 73 publications
(119 reference statements)
0
11
0
Order By: Relevance
“…used in our study, we suggest that fruit bats will disperse viable seeds through faeces and spats as a result of the change in roost sites, as indicated in several studies (Djossa et al, 2008;Heer et al, 2010;Izhaki et al, 1995;Tang et al, 2007). Furthermore, Shilton et al (1999) observed that captured fruit bats in cages defecated after the cages were cleaned, suggesting that fig seeds could be retained in the digestive tracts of fruit bats for longer periods and thus over long distances based on their movement between foraging and roosting sites shown in other studies (Monadjem et al, 2010;Mphethe et al, 2023;Rollinson et al, 2013). Beyond enhancing germination rates and speeding up the emergence of seedlings, studies have also suggested the importance of seed ingestion by fruit bat and fruit-eating bat species for the restoration of degraded areas because they typically cover a relatively large area and long distances for foraging (Heer et al, 2010;Rollinson et al, 2013;van Toor et al, 2019) enhancing gene flow between populations from different habitat fragments (Pulzatto et al, 2018).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…used in our study, we suggest that fruit bats will disperse viable seeds through faeces and spats as a result of the change in roost sites, as indicated in several studies (Djossa et al, 2008;Heer et al, 2010;Izhaki et al, 1995;Tang et al, 2007). Furthermore, Shilton et al (1999) observed that captured fruit bats in cages defecated after the cages were cleaned, suggesting that fig seeds could be retained in the digestive tracts of fruit bats for longer periods and thus over long distances based on their movement between foraging and roosting sites shown in other studies (Monadjem et al, 2010;Mphethe et al, 2023;Rollinson et al, 2013). Beyond enhancing germination rates and speeding up the emergence of seedlings, studies have also suggested the importance of seed ingestion by fruit bat and fruit-eating bat species for the restoration of degraded areas because they typically cover a relatively large area and long distances for foraging (Heer et al, 2010;Rollinson et al, 2013;van Toor et al, 2019) enhancing gene flow between populations from different habitat fragments (Pulzatto et al, 2018).…”
Section: Discussionmentioning
confidence: 74%
“…They, therefore, are potentially transported farther, enhancing seed dispersal and likely resulting in the production of seed rain (Jordaan et al., 2012; Tang et al., 2007). Several researchers have also reported that fruit bats and fruit‐eating bats commute between fruiting trees and their feeding roosts and often defecate on their way to and from fruiting trees, thus depositing seeds along their way (Heer et al., 2010; Mphethe et al., 2023; Muscarella & Fleming, 2007; Pulzatto et al., 2018; Rollinson et al., 2014; Seltzer et al., 2013; Tang et al., 2007; pers. obs.).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vegetation is also an important predictor that influences habitat suitability for fruit bat species. Dry and moist deciduous forests, native plants, and angiosperm plants, as well as caves, provide suitable roosting habitat for R. aegyptiacus and E. labiatus (Happold & Happold, 2013;Majumdar et al, 2016;Mphethe et al, 2023;Roberts et al, 2016). Different ecoregions, landscapes, and vegetation all have an impact on fruit bat dispersal patterns because they offer food and roosting protection (Frick et al, 2020;Hughes et al, 2012;Kafash et al, 2022).…”
Section: F I G U R Ementioning
confidence: 99%